Organizational and economic algorithms of digital audit and digital controlling in the management system of large industrial enterprises - M. V. Belyaeva (Путеводитель предпринимателя, 2020)
Goals. Based on the analysis of literature sources, as well as international experience in the development of digital audit and digital controlling technologies, to study organizational and economic algorithms of digital audit and digital controlling in the management system of large industrial enterprises Methodology. The methodical basis of this article is the literature on the construction of organizational and economic algorithms of digital audit and digital controlling. Results. This article defines the role and purpose of digital audit and digital controlling. The analysis of modern organizational and economic algorithms of digital audit and digital controlling is carried out. The role ofdigital audit and digital controlling in the management system of a large industrial enterprise is considered. Conclusions/relevance. The world continues to change and the speed of change increases. It is useless to struggle with the concept of universal digitalization - it must be accepted and understood how it can be integrated. However, digitalization is less about technology and more about culture, about change and about the model of interaction. Of particular importance today are organizational and economic algorithms ofdigital audit and digital controlling. It is the competent construction of these algorithms that is the source of reliability and importance of modern enterprise management.